Esoterism in Literature and in Literary History - Daujotytė-Pakerienė, iktorija (Literatūra, 2015)
The article is inspired by intensified attention to the esoteric in humanities. The author tries to find out what are the roots of esoterism in tradition, what are the links between esoterism and an idealistic explanation of art and creative nature. The connection between esoterism and modernism is being stressed. The main attention is paid to Lithuanian literature of the beginning of the 20th century: it programically declared the longing towards the secret, the mystical. Links are established between esoterism, occultism, mysticism and partly hermetism.From the methodological point of view, the main orientation is towards phenomenological notion of literature and literary process. The creative activity of consciousness has many various levels of experience, however, it is impossible divide this activity into rational levels of reason and result. In the literary process there are important not only external (social, political, economical factors) but internal movements of consciousness as well. They are linked with the state of longing, anxiety, seeking, more or less explainable, and with personal experience of artists.Esoterism is rooted in ancient mysterious religions and shows the secretness of religious doctrines and cults. In cultural history esoterism denotes an attention to the mystical, unexplainable (both in personal life and in the world); the attention is of a more general type. Magic and ocultism in some cases are the broader, in other cases the narrower frames of esoterism.